Masyarakat Minahasa pada Abad ke–XIX: Sketsa Perubahan dan Transformasi - Alex J. Ulaen (Antropologi Indonesia, 1995)
This article is concerned with social change and cultural transformation in Minahasa in the 19th century. These changes happened because of the introduction of new cultural traits from outside Minahasa by the Dutch, Moslem traders, Christian evangelist, etc. the author claims that agricultural transformation is the main modality of the changes. The domestication of plants, i.e. rice and coffee, introduces by the Dutch East Indies Company (VOC)became important commodities that were made in order to secure sufficient rice supply for their soldiers in the Moluccas. In the 1850s coffee became the main cash crop for Dutch trading through Culture System, which forced the Minahasans to expand their lands and planted it with coffee. The second part of 19th century marked the institutionalization of Christianity, the fusion of districts which formerly were the traditional political units, the bureaucratization of (traditional) local government with the appointment of civil servants, and the introduction of formal education.